2022
DOI: 10.31004/cendekia.v6i2.1452
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan E-modul Matematika pada Materi Barisan dan Deret Berbantuan Smart App Creator untuk Siswa SMA/SMK

Abstract: Perkembangan teknologi telah menuntut guru untuk lebih berinovasi dalam proses pembelajaran. Dengan itu perlu adanya media pembelajaran yang tidak terbatas untuk dipelajari disekolah yaitu berupa E-modul pembelajaran agar siswa dapat belajar kapan saja dan dimana saja. Untuk itu peneliti akan mengembangkan aplikasi pembelajaran materi barisan dan deret kelas XI SMA/SMK.  Jenis penelitian yang digunakan yaitu R&D dengan model ADDIE (Analyze, Design, Develovment, Implementation, dan Evaluation). Adapun subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…From the explanation above, it can be concluded that mathematics learning media can enhance students' creative thinking abilities (Lailatul Auliah, Syaiful, 2020). In this context, Alpiani (2022) suggests that learning media created with creativity can assist teachers and students in addressing mathematical problems, particularly those related to lines and series. For example, the wick editor learning media has been proven to be valid, practical, and effective in enhancing students' creative thinking abilities.…”
Section: E Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…From the explanation above, it can be concluded that mathematics learning media can enhance students' creative thinking abilities (Lailatul Auliah, Syaiful, 2020). In this context, Alpiani (2022) suggests that learning media created with creativity can assist teachers and students in addressing mathematical problems, particularly those related to lines and series. For example, the wick editor learning media has been proven to be valid, practical, and effective in enhancing students' creative thinking abilities.…”
Section: E Evaluationmentioning
confidence: 99%
“…Arithmetic sequence is a sequence of numbers that has a certain pattern in the form of addition and has the same difference, while arithmetic sequence is the sum of the terms in the arithmetic sequence (Kemendikbud, n.d.). The material of rows and series is very important material to be learned by students because it is very useful when students enter the world of work (Alpiani et al, 2022). In addition, Alpiani et al (2022) mentioned that there are some student difficulties with the material of rows and series, namely in determining the formula for the nth term of arithmetic and geometric rows, understanding the concept of the first term and understanding the problems of rows and series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic modules (e-modules) are electronic versions of learning tools designed using software according to student needs (Alpiani et al, 2022). E-modules are interactive and serve as online educational resources to aid in learning (Pramana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Disimpulkan bahwa penelitian ini berhasil menciptakan articulate story pada sistem tata surya telah memenuhi kriteria valid, praktis dan efektif. b. Penelitian yang dilakukan oleh(Alpiani et al, 2022b) yang berjudul "Pengembangan E-Modul Matematika pada Materi Barisan dan Deret Berbantuan Smart App Creator untu Siswa SMA/SMK", Tujuan dari penelitian ini adalah mengunakan metode Research and Development dengan metode ADDIE untuk menciptakan media pembelajaran berbasis e-modul yang bisa digunakan oleh siswa untuk bisa belajar dimana saja dan kapan saja. Dari hasil penelitian ini didapatkan hasil berupa e modul dengan prosentase keefektifan ketuntasan sebesar 76% , dikatakan layak dan praktis sebagai pendukung pembelajaran.…”
unclassified